Peningkatan Kemampuan Balita Melalui Pemantauan Tumbuh Kembang Penggunaan Kuesioner Pra Skreening Perkembangan (KPSP) - Endang Surani (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
The quality of child development must be improved since toddlers. One tool that can be used to monitor the development of toddlers carefully, can be used Pre Development Screening Questionnaire (KPSP).The number of children under five around UNISSULA is 9 children. The problem is that most mothers do not understand correctly in stimulating and assessing their child's growth. The output produced is the application of science and technology and increasing the quantity and quality of child development.Implementation of activities with the transfer of science and technology is carried out directly on 29-30 November 2017 targeting toddlers and their mothers in the D3 Midwifery Study Program FK Unissula Semarang. The form of transfer of science and technology begins with pre-test and ends with post-test, education is delivered by providing material about the development and stimulation of children, followed by growth assessment using KPSP.The level of understanding of mothers from the pre-test and post-test results increased by 4.55%, mothers of toddlers know how to stimulate the development of their toddlers. The most important thing from this activity is the mothers will transfer or teach other mothers of children under five, both at home and in the office.